2012
DOI: 10.3184/095422912x13325261626531
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of trace metals, peptide ligands of trace metals and mercury speciation in home prepared bread

Abstract: Bread represents an important source of trace elements in the human diet. This study is focused on home prepared bread in the Czech Republic. The amounts of Cu, Mo, Mn, Ni and Zn (total and soluble in Tris-HCl buffer, pH 7.5), Cd, Co, Fe, Pb and Tl (total only) as well as Hg (total and soluble in mercaptoethanol-HCl mixture) in raw materials and baked bread were determined using ICP-MS. Moreover, the speciation of elements was investigated using HPLC/ICP-MS. Isolated peptide ligands of the trace elements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
0
1
Order By: Relevance
“…Concerning the level of lead in the different brands: B2 and B3 contents were more than 2.5 fold higher than B1 (74, 203, and 260 µg/kg, respectively). The order of magnitude of B1 is in accordance with Turkish, Iranian, Ethiopian, and Spanish studies on bread [52,59] and 7 fold more higher than in data on the Czech Republic [44]. The B3 pita lead content was 32 fold higher than Lebanese data [13] which focused on Beirut.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Concerning the level of lead in the different brands: B2 and B3 contents were more than 2.5 fold higher than B1 (74, 203, and 260 µg/kg, respectively). The order of magnitude of B1 is in accordance with Turkish, Iranian, Ethiopian, and Spanish studies on bread [52,59] and 7 fold more higher than in data on the Czech Republic [44]. The B3 pita lead content was 32 fold higher than Lebanese data [13] which focused on Beirut.…”
Section: Discussionsupporting
confidence: 82%
“…Same as for Cd, bread is not the main source of Hg, for which it is fish and seafood, which is a concern for high fish consumers [17] and, particularly, pregnant women [15]. We found between 0.70 and 0.89 µg/kg of Hg in Lebanese pita which is by far less than in the study of Mestek and co-workers [44] who found 13 µg/kg of Hg in bread in the Czech Republic.…”
Section: Discussioncontrasting
confidence: 58%
“…Beside the bread quality as the main diet source in developing countries, its safety needs to be confirmed and examined in terms of known toxic as trace elements. Bread is also an important and major source of heavy metals (Mestek et al, 2015), this is due to the high consumption of it. But their concentrations depend on many factors.…”
Section: Introductionmentioning
confidence: 99%